Seeking Clarity in Murky Waters: Nuances of Equity and Social Justice From a Teacher Perspective - Chan, Elaine J. (Frontiers in Education, 2022)
In this study, I examine ways in which ideas of equity and social justice may play out in nuanced ways for a teacher in her English classroom in a diverse, high needs school in a Midwestern city. I consider ways in which issues of equity and social justice might unfold for students in the implementation of school curriculum at the secondary level. Examples of equity and social justice from interactions between a teacher and her students reveal complexities of how these issues might be understood and addressed by a teacher as she works with her students. Complexities of “teacher knowledge” (Clandinin & Connelly, 1996) as a classroom teacher attempts to acknowledge her students’ social and cultural backgrounds in her curriculum while also implementing curriculum that meets requirements established by her school board, offer insight into challenges a teacher might encounter while working with students of diverse backgrounds in a school context.